SINCRETIC SEMIOTIC THE ANCIENT INDONESIAN MOSQUE TOMBHOUSE Case study SENDANG DUWUR-EAST JAVA - Wiranto Wiranto (Dimensi: Journal of Architecture and Built Environment, 2002)
Mosque is a place for worship, spirit, contemplation, but above all, Mosque is "a gate way". Sendang Duwur Mosque and Tombhouse is an Islamic antiquity as the product of syncretism process between traditional Javanese architecture - Hindunese/Budhanese - foreign Islamic which born early Mosque in Java. The semiotic and syncretic of Indonesian Mosque and Tombhouse also integrated some principles of the Javanese cosmology blend with the concept of Islamic Architecture, which resulted a symthesis of both traditional and new idea. It manifested in the type of ancient Mosque and tombhouse Sendang Duwur,which is original types ,specific with identity. Abstract in Bahasa Indonesia : Pada hakekatnya peran suatu Masjid adalah sebagai tempat beribadat, tempat menemukan kekuatan bathin ,tempat samadi, namun diatas itu semua peran Masjid adalah sebagai suatu "gerbang". Masjid makam Sunan Sendang Duwur adalah bangunan purbakala sebagai salah satu produk proses sinkretisme arsitektur Tradisional Jawa - Hindu/Budha - dan Islam .yang selanjutnya melahirkan wujud awal Masjid utama diJawa. Semiotic dan sinkretis Masjid makam di Indonesia juga mengintegrasikan beberapa prinsip Kosmologi Jawa yang diramu secara harmonis dengan konsep arsitektur Islam ,yang selanjutnya menghasilkan suatu sinthesa tradisional sebagai ide baru. Jabaran tersebut terlihat pada Masjid makam Sunan Sendang Duwur yang menampilkan type yang aseli, spesifik dan beridentitas. Kata kunci: sinkretisme, semiotic, Masjid, Gapura, Nilai.